You are on page 1of 6

How to Find Bases for Jordan Canonical Forms

Now that we know how to nd the Jordan canonical form of various matrices, let's look at nding the
bases from which these forms arise. Here is one way to go about this:

The Idea of the Method

Recall for a linearQ
transformation T : V → V , we computed a matrix A for T and found the characteristic
polynomial pA (x) = m k=1 (x − λk )
αk
with λk 6= λj for k 6= j and αk ≥ 1 for all k. We then, for each i, set
di = dim N ((A − λk I) ) (d0 = 0) from which we found the Jordan canonical form.
i

The idea for nding a basis relates to the proof of why a Jordan canonical form exists. What we seek to
do is nd a largest possible set of chains (or cycles) of the form {x, (T − λk I)(x), . . . , (T − λk I)p−1 (x)} which
are linearly independent. By the proof of Jordan canonical form, the number and lengths of these chains
can be found from the numbers d0 , . . . , d`k . Indeed, let λ = λk be a xed eigenvalue for T (α = αk , ` = `k )
consider the transformation (T − λ)|Wλ on Wλ , the generalized eigenspace of T corresponding to λ. Then,
let ei = dim R((T − λ)|iWλ ) = dim Wλ − di (by rank nullity) for 0 ≤ i ≤ `. Then, ei is a decreasing sequence
with e0 = dim Wλ , e` = 0, and e`−1 6= 0.

We construct a basis as follows: rst, nd a basis for R((T − λ)|W `−1
λ
), say {z1 , . . . , zm`−1 } (here m`−1 =
e`−1 ). Then, each zj will be of the form zj = (T − λ) (xj ) for some x1 , . . . , xm`−1 ∈ Wλ . For each j , we
`−1

will get the set {xj , (T − λ)(xj ), . . . , (T − λ)`−1 (xj )}. The union of these sets is guaranteed to be linearly
independent by theorems from the book and/or class. Add each of these to βλ , our basis-under-construction
for Wλ .

If card(β) = dim(Wλ ), then we're done. If not, then we need to nd more chains. For this, we compare
the size of the linearly independent sets within R((T − λ)|iWλ ) we have already found with these chains
to the actual dimensions ei . From the sets generated, we have ei ≥ (` − i)e`−1 (the union of the sets
{(T − λ)i (xj ), . . . , (T − λ)`−1 (xj )} is linearly independent, lies in R((T − λ)|iWλ ), and has size (` − i)e`−1 . If
p − 1 is the largest index for which ep−1 > (` − p)e`−1 , this indicates that there is at least one more chain
of length p to be found. To nd these, we consider R((T − λ)|W p−1
λ
). This space already has the linearly
independent set j=1 {(T − λ) (xj ), . . . , (T − λ) (xj )} in it; so we can extend this to a basis by adding,
Sm`−1 p−1 `−1

say, {y1 , . . . , ymp−1 }. Then, each yj is of the form yj = (T − λ)p−1 (vj ) for some v1 , . . . , vmp−1 ∈ Wλ , and in
this way we get more linearly independent sets {vj , (T − λ)(vj ), . . . , (T − λ)p−1 (vj )} which, when added to
our βλ , will still produce a linearly independent set. Continuing in this fashion (ie if dim Wλ = card(βλ ),
stop, else look for smaller chains by comparing dimensions), we will produce a basis βλ in which [T |Wλ ]βλ is
in Jordan canonical form. Doing this for each λ gives a Jordan canonical form basis for V .

If the above is intimidating, don't worry; this is usually best seen with examples. One thing that helps
is if you know a Jordan canonical form (eg by the method from the last pdf), you know how many chains
to look for and what length they are. Indeed, each r × r Jordan block will correspond to a chain of length r
(ie {x, (T − λ)(x), . . . , (T − λ)r−1 (x)} with (T − λ)r (x) = 0). All our process then needs to do is make sure
the chains are linearly independent.

Rough Step-by-Step Outline of the Method

(i) Let A be a matrix for T and nd pA (x) and factor it as before. For each eigenvalue λ, nd the d0i s.
(ii) Use the d0i s to nd the e0i s. These will tell you the various chain sizes and where to look for them.
(ii') Alternatively, compute the Jordan canonical form of the transformation as before and use this to 
nd the chain sizes and locations.
(iii) Find the chains by computing various bases of ranges (together with their preimages), null spaces,
and linearly independent sets that have been created previously during this step. The chain structure will
guide your computations as above. This is by far the most computation-intensive step.

1
(iv) Applying (iii) for each λ will give a basis βλ for each generalized eigenspace Wλ . Combining these
bases will give the desired Jordan canonical form basis (up to rearrangement).

Examples

Let's nd Jordan canonical form bases for the examples from last time.
 
2 2 3
Example 1. Let T be a transformation with matrix A =  1 3 3 .
−1 −2 −2
 
1 2 3
Recall pA (x) = (x − 1)3 . We had A − I =  1 2 3  which has rank 1 and (A − I)2 = 0. Thus,
−1 −2 −3
d0 = 0, d1 = 2, and d2 = 3, so e0 = 3, e1 = 1, and e0 = 0. We see {(1, 1, −1)} is a basis for R((A − I)). We 
nd (x, y, z) with (A − I)(x, y, z) = (1, 1, −1) (for typesetting let's use this notation as opposed to writing
the vector (x, y, z) as a column vector). By inspection, (1, 0, 0) works, so our basis-to-be β1 is
{(1, 0, 0), (1, 1, −1)}

Now, e0 = 3 > 2 = card({(1, 0, 0), (1, 1, −1)}), so we can nd a chain of length 1 linearly independent
from {(1, 0, 0), (1, 1, −1)}. Indeed, this amounts to nding (x, y, z) such that {(1, 0, 0), (1, 1, −1)} is linearly
independent and such that (T −I)(x, y, z) = 0. We see (A−I)(x, y, z) = (x+2y +3z, x+2y +3z, −x−2y −3z)
so (−2, 1, 0) works. Hence, β1 = {(1, 0, 0), (1, 1, −1), (−2, 1, 0)} is a basis for which T |W1 is in Jordan canon-
ical form.

 As 1 is the only eigenvalue of A, this is a Jordan canonical form basis for T . Indeed, we see [T ]β1 =
1 0 0 1 0 0
1 1 0 (if we wish to have 0 1 1 from last time, we need only reorder the chains and the elements
0 0 1 0 0 1  
1 0 0
within the chains; if β 0 = {(−2, 1, 0), (1, 1, −1), (1, 0, 0)}, then [T ]β 0 = 0 1 1)
0 0 1
 
1 0 0 0 0
 1 −1 0 0 −1
Example 2. Let T be a transformation with matrix A =   1 −1 0 0 −1.
 

0 0 0 0 −1
−1 1 0 0 1
Recall pA (x) =x4 (x − 1). We had
 
1 0 0 0 0
1
 −1 0 0 −1

A−0=
1 −1 0 0 −1

0 0 0 0 −1
−1 1 0 0 1

with rank 3,  
1 0 0 0 0
1 0 0 0 0
(A − 0)2 = 
 
1 0 0 0 0
1 −1 0 0 −1
−1 0 0 0 0

2
with rank 2, and  
1 0 0 0 0
1 0 0 0 0
(A − 0)3 = 
 
1 0 0 0 0
1 0 0 0 0
−1 0 0 0 0
with rank 1. Hence, for the eigenvalue λ = 0, we have d0 = 0, d1 = 2, d2 = 3, d3 = 4 = dim W0 and e0 = 4,
e1 = 2, e2 = 1, e3 = 0. Thus, we wish to nd a basis for R(T |2W0 ). That is, as this as dimension 1 and
T |3W0 = 0 (on this subspace), a vector (a, b, c, d, e) with A2 (a, b, c, d, e) 6= 0 but A3 (a, b, c, d, e) = 0.

We have A2 (a, b, c, d, e) = (a, a, a, a − b − e, −a) and A3 (a, b, c, d, e) = (a, a, a, a, −a) so for A3 (a, b, c, d, e)
to be 0, we must have a = 0. Then, a − b − e 6= 0, so our vector in R(T |2W0 ) is of the form (0, 0, 0, x, 0). We
take (0, 0, 0, −2, 0) = A2 (0, 1, 0, 0, 1). Thus, the chain we get is
{(0, 1, 0, 0, 1), A(0, 1, 0, 0, 1), A2 (0, 1, 0, 0, 1)} = {(0, 1, 0, 0, 1), (0, −2, −2, −1, 2), (0, 0, 0, −2, 0)}

This gives us the linearly independent set {(0, −2, −2, −1, 2), (0, 0, 0, −2, 0)} in R(T |W0 ) and, as this space
has dimension e1 = 2, there are no chains of length 2 to be found here. Now, {(0, 1, 0, 0, 1), (0, −2, −2, −1, 2), (0, 0, 0, −2, 0)}
is a linearly independent set in W0 which has dimension 4, and so we are missing a chain of length 1. That
is, there is a vector (a0 , b0 , c0 , d0 , e0 ) with A(a0 , b0 , c0 , d0 , e0 ) = 0 and such that
{(a0 , b0 , c0 , d0 , e0 ), (0, 1, 0, 0, 1), (0, −2, −2, −1, 2), (0, 0, 0, −2, 0)}
is a linearly independent set in W0 (and hence a basis). We see
A(a0 , b0 , c0 , d0 , e0 ) = (a0 , a0 − b0 − e0 , a0 − b0 − e0 , −e0 , −a0 + b0 + e0 )
so a0 = e0 = 0 and hence b0 = 0. Thus, we are looking for (0, 0, c0 , d0 , 0) such that
{(0, 0, c0 , d0 , 0), (0, 1, 0, 0, 1), (0, −2, −2, −1, 2), (0, 0, 0, −2, 0)}
is linearly independent. By inspection, we see (0, 0, 1, 0, 0) works (such a solution has to exist and (0, 0, 0, −2, 0)
allows us to subtract o the d0 component). Thus,
β0 = {(0, 0, 1, 0, 0), (0, 1, 0, 0, 1), (0, −2, −2, −1, 2), (0, 0, 0, −2, 0)}
is a Jordan basis for W0 .

We also need a Jordan basis for W1 , but
 this is easy as dim W
1 = 1. Thus, we only need to nd
0 0 0 0 0
 1 −2 0 0 −1 
(a, b, c, d, e) ∈ N (A − I). We see A − I =   and so (A − I)(a, b, c, d, e) = (0, a −
 
 1 −1 −1 0 −1 
0 0 0 −1 −1
−1 1 0 0 0
2b − e, a − b − c − e, −d − e, −a + b). The only solution for this with a = 0 is (0, 0, 0, 0, 0), so we may
take a = 1. Then, this gives b = 1, e = −1, c = 1, d = 1. Thus, (1, 1, 1, 1, −1) is our desired vector, so
β1 = {(1, 1, 1, 1, −1)} is a basis for W1 . Hence,
β = β1 ∪ β0 = {(1, 1, 1, 1, −1), (0, 0, 1, 0, 0), (0, 1, 0, 0, 1), (0, −2, −2, −1, 2), (0, 0, 0, −2, 0)}
is a Jordan canonical form basis for T . Indeed,
 
1 0 0 0 0
0 0 0 0 0
 
0
[T ]β =  0 0 0 0
0 0 1 0 0
0 0 0 1 0

3
If we wish to recover the form from last time, we need only reorder the basis (switch order within chains and
some chain orders). Indeed, if
β 0 = {(1, 1, 1, 1, −1), (0, 0, 1, 0, 0), (0, 0, 0, −2, 0), (0, −2, −2, −1, 2), (0, 1, 0, 0, 1)}

then  
1 0 0 0 0
0 0 0 0 0
 
[T ]β 0 0
= 0 0 1 0
0 0 0 0 1
0 0 0 0 0

 
1 0 0 0 0 0
0
 0 0 0 −1 1

−1 −1 1 1 −1 1
Example 3. Let T be a transformation with matrix A = 
 
0 0 0 1 0 0
0 1 0 0 2 0
0 0 0 0 0 1
Recall pA (x) = (x − 1)6 . We have
 
0 0 0 0 0 0
 0 −1 0 0 −1 1
 
−1 −1 0 1 −1 1
A−I =
0

 0 0 0 0 0 
0 1 0 0 1 0
0 0 0 0 0 0

with rank 3,  
0 0 0 0 0 0
0
 0 0 0 0 −1
0 0 0 0 0 −1
(A − I)2 = 
0

 0 0 0 0 0
0 0 0 0 0 1
0 0 0 0 0 0
with rank 1, and (A − I)3 = 0. Thus, for λ = 1, d0 = 0, d1 = 3, d2 = 5, and d3 = 6. This gives e0 = 6,
e1 = 3, e2 = 1, and e3 = 0. Hence, we wish to nd a basis for R((T − I)2 ). Indeed, such a basis has e2 = 1
elements. We see (A − I)2 (a, b, c, d, e, f ) = (0, −f, −f, 0, f, 0), so for this to be nonzero we must have f 6= 0.
Thus, (0, −1, −1, 0, 1, 0) = A2 (0, 0, 0, 0, 0, 1) will work. Hence, we get the chain
{(0, 0, 0, 0, 0, 1), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)}

Now, in R((T − I)) we have 2 linearly independent vectors so far ((0, 1, 1, 0, 0, 0) and (0, −1, −1, 0, 1, 0)).
This space has dimension e1 = 3, so there is another chain to be found here. That is, we can nd
(a, b, c, d, e, f ) ∈ R((T − I)) such that

{(a, b, c, d, e, f ), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)}

is linearly independent. Such a vector would satisfy (A − I)(a, b, c, d, e, f ) = 0 (as the chain only has length
2). We see that
(A − I)(u, v, w, x, y, z) = (0, −v − y + z, −u − v + x − y − z, 0, v + y, 0)

so we must have
(a, b, c, d, e, f ) = (0, −v − y + z, −u − v + x − y − z, 0, v + y, 0)

4
for some (u, v, w, x, y, z),
(0, −b − e + f, −a − b + d − e − f, 0, b + e, 0) = (0, 0, 0, 0, 0, 0),

and such that
{(a, b, c, d, e, f ), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)}
is a linearly independent set. We see then that b + e = 0, so f = 0. Thus, −a + d = 0, so d = a. Hence, our
vector is of the form
(a, b, c, a, −b, 0) = (0, −v − y + z, −u − v + x − y − z, 0, v + y, 0)

From this a = 0, so our vector has the form (0, b, c, 0, −b, 0). We need
{(0, b, c, 0, 0 − b, 0), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)}

to be linearly independent. Using (0, −1, −1, 0, 1, 0), we can make this (0, 0, c − b, 0, 0, 0, 0) (we need to
keep the (0, B, C, 0, 0, −B, 0) form to satisfy the other equations), and so we see (0, 0, 1, 0, 0, 0) works.
Then, from (0, 0, 1, 0, 0, 0) = (0, −v − y + z, −u − v + x − y − z, 0, v + y, 0), we can take (u, v, w, x, y, z) =
(0, 1, 0, 1, −1, 0). Thus, we have the chain {(0, 1, 0, 1, −1, 0), (0, 0, 1, 0, 0, 0)} which, when added to our other
chain {(0, 0, 0, 0, 0, 1), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)} gives us
{(0, 1, 0, 1, −1, 0), (0, 0, 1, 0, 0, 0), (0, 0, 0, 0, 0, 1), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)}

Now we have 5 linearly independent vectors in W0 , but dim W0 = e0 = 6, so we are missing a chain of
length one. That is, there is a vector (a, b, c, d, e, f ) such that (A − I)(a, b, c, d, e, f ) = 0 and such that
{(a, b, c, d, e, f ), (0, 1, 0, 1, −1, 0), (0, 0, 1, 0, 0, 0), (0, 0, 0, 0, 0, 1), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)}

is linearly independent. We see from the above that
(A − I)(a, b, c, d, e, f ) = (0, −b − e + f, −a − b + d − e − f, 0, b + e, 0)

so we must have b + e = 0, f = 0, and −a + d = 0, so (a, b, c, d, e, f ) = (a, b, c, a, −b, 0). Thus, we need
{(a, b, c, a, −b, 0), (0, 1, 0, 1, −1, 0), (0, 0, 1, 0, 0, 0), (0, 0, 0, 0, 0, 1), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)}

to be linearly independent. With (0, −1, −1, 0, 1, 0) + (0, 0, 1, 0, 0, 0) = (0, −1, 0, 0, 1, 0) we can zero out
the 2nd and 5th coecients. With (0, 0, 1, 0, 0, 0) we can zero out the 3rd coecient. Hence, we can take
(1, 0, 0, 1, 0, 0).

Adding this to our previous chains, we get the basis
β = {(1, 0, 0, 1, 0, 0), (0, 1, 0, 1, −1, 0), (0, 0, 1, 0, 0, 0), (0, 0, 0, 0, 0, 1), (0, 1, 1, 0, 0, 0), (0, −1, −1, 0, 1, 0)}

our Jordan canonical basis. In this basis,
 
1 0 0 0 0 0
0 1 0 0 0 0
 
0 1 1 0 0 0
[T ]β = 
0

 0 0 1 0 0
0 0 0 1 1 0
0 0 0 0 1 1

If we wish to recover the form from last time, we can reorder the basis as
β 0 = {(1, 0, 0, 1, 0, 0), (0, 0, 1, 0, 0, 0), (0, 1, 0, 1, −1, 0), (0, −1, −1, 0, 1, 0), (0, 1, 1, 0, 0, 0), (0, 0, 0, 0, 0, 1), }

5
In this basis,  
1 0 0 0 0 0
0 1 1 0 0 0
 
0 0 1 0 0 0
[T ]β 0 =
0

 0 0 1 1 0
0 0 0 0 1 1
0 0 0 0 0 1

6